Public Geospatial Data for Groundwater Governance: The Brazilian Case - Silva, César de Oliveira Ferreira [UNESP]; Manzione, Rodrigo Lilla [UNESP] (My University, 2021)
The present work presents two databases available in Brazil related to groundwater governance applications, exposing their applicability, gaps and potential geoethical discussions. The first database is the Rural Environmental Registry (CAR), which is a national electronic public record, mandatory for all rural properties. The second database is the Groundwater Information System (SIAGAS) developed by the Geological Survey of Brazil (CPRM), which consists of a continuously updated database of wells. CAR has a record of 1,892,067 water springs located within rural properties and SIAGAS has 322,922 registered wells. Publicity of CAR data is ensured by law. Both are public databases, so their use does not generate legal conflicts. CAR data is self-reported (by landowners) and requires validation by the government. For this reason, its use currently requires care to avoid distortions caused by errors in the georeferencing of springs. SIAGAS also has a small number of wells registered, and it is estimated that 88% of wells in Brazil are clandestine. SIAGAS and CAR are examples of databases of great applicability to groundwater governance, both by government initiatives, which require validation and improvements in order to be expanded and applied with greater reliability.
Keywords: CAR; Computation; SIAGAS; Springs; Wells